Synthesis of Acrolein from Glycerol Using FePO4 Catalyst in Liquid Phase Dehydration - Abidin, Akhmad Zainal; Afandi, Rani Guslianti; Graha, Hafis Pratama Rendra (Journal of Engineering and Technological Sciences, 2016)
Acrolein is currently produced using propylene from crude oil while its price and scarcity are increasing. A renewable material such as glycerol is an attractive alternative for acrolein production. It can be obtained from crude palm oil (CPO) and is a byproduct of biodiesel production. Besides being able to compete economically, glycerol is an environmentally friendly material. The purpose of this study is to synthesize acrolein from glycerol using FePO4 catalyst in liquid phase dehydration. The catalyst was prepared by three different methods: hydrothermal (catalyst A), deposition at Fe/P = 1.15 (catalyst B), and deposition at Fe/P = 1.20 (catalyst C). The experimental reaction temperature was varied at 220, 240 and 260Â Â°C under constant atmospheric pressure. The results showed that catalyst C provided the best yield (91%), followed by catalyst A (90%) and catalyst B (82%). The increasing reaction temperature showed a tendency to increase the yield of acrolein, while the presence of oxygen reduced the yield of acrolein and allowed the reaction to produce more side products such as glycerol propanal, acetaldehyde, and propionate. Catalyst reuse without any regeneration resulted in a yield profile of acrolein that continued to decline.